Usia ibu dan jumlah anak berhubungan dengan kejadian beban gizi ganda pada tingkat rumah tangga di desa dan kota di Indonesia - Nur Fitri Widya Astuti; Emy Huriyati; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Maternal age and number of children are associated with the incidence of a double burden of malnutrition at the household level in rural and urban areas in IndonesiaBackground: Double burden of malnutrition is a nutritional problem where two nutritional problems occur at the same time and this can happen at the household level. The diversity of community characteristics causes differences in the incidence of the double burden of malnutrition at the household level in people living in rural and urban areas in Indonesia.Objective: To determine the associated factors with the incidence of double burden malnutrition at the household level in rural and urban areas in Indonesia.Methods: This study with a cross-sectional design used secondary data from the fifth wave of the Indonesia Family Life Survey (IFLS). The sample in this study was 6,468 households. The double burden of malnutrition at the household level is defined as a household in which there is at least one pair of mother and child aged 2-18 years that has underweight and or overweight/obese. Maternal factors, household economic status, number of children, and regional area are independent variables in this study. A logistic regression test was used to perform statistical analysis.Results: The prevalence of double burden malnutrition at the household level in urban areas was higher than in rural areas (8.70%) and 7.77%). Factors that were significantly (p<0.05) associated with the incidence of double burden malnutrition at the household level in rural areas were maternal age, mother's education, economic level, number of children, and regional living of the household, while in urban areas were maternal age and number of children.Conclusions: Maternal age and the number of children are two significant factors associated with the incidence of double burden malnutrition at the household level in rural and urban areas in Indonesia.